P424 SMALL HEART AND SINGLE CORONARY ARTERY IN A YOUNG PATIENT WITH CHRONIC FATIGUE SYNDROME: A CASE REPORT. (18th May 2022) - Poleggi, C; Perfetti, S; Restelli, D; Perna, A; Donato, R; Di Bella, G
Abstract: Introduction: Chronic fatigue syndrome/Myalgic encephalomyelitis (CFS/ME) is a clinically defined condition reported mostly in adults, characterized by severe and disabling fatigue limiting normal daily activities for at least 6 months accompanied by multiple unexplained symptoms including self–reported impairments in concentration and short–term memory, sleep disturbances, and musculoskeletal pain. Although rarely considered to have cardiac dysfunction, CFS/ME patients frequently have reduced stroke volume with a significant inverse relation between cardiac output and post–exertional malaise severity. We describe a case of a young man affected by CFS/ME and small heart with incidental findings of anomalous origin of the left main coronary artery (LMCA). Case Presentation: A 19–year–old Caucasian male presented to our clinic complaining weakness, lack of concentration and excessive daytime sleepiness. Medical history included CFS/ME, D hypovitaminosis, inflammatory bowel disease associated with pancreatic insufficiency. Physical examination including cardiovascular auscultation was unremarkable, with normal blood pressure and heart rate. Electrocardiogram showed sinus rhythm at 75 bpm without any repolarization abnormalities. Echocardiogram revealed reduced diameters of left ventricle (LV) (end–diastolic diameter 36 mm), normal aortic root dimensions and, in a five–chamber apical view, a binary structure that seemed to cross the aorta perpendicularly to its long axis. Cardiac magnetic resonance (CMR) found significantly reduced LV stroke volume (34 ml/m2; normal values 44–68 ml/m2) and end–diastolic volume (57 ml/m2; normal values 68–103 ml/m2) together with reduced end–diastolic wall mass (51 g/m2; normal values 59–93 g/m2). Also, right ventricle (RV) volumes were reduced: stroke volume (32 ml/m2; normal values 40–72 ml/m2), end–diastolic volume (62 ml/m2; normal values 68–114 ml/m2). In addition, the exam confirmed the anomalous origin of LMCA stemming from the proximal segment of right coronary artery and following a retro–aortic course. Conclusions: Not sufficient consideration was given to cardiovascular involvement in patients with CFS/ME, although many of signs and symptoms are suggestive of cardiovascular dysfunction. This case highlights that CFS/ME together with small heart is a condition possible also in young people. More studies and reports could be necessary to better define the association with cardiac congenital anomalies and CFS/ME.